2016
DOI: 10.1093/trstmh/trv110
|View full text |Cite
|
Sign up to set email alerts
|

Higher physiopathogenicity byFasciola giganticathan by the genetically closeF. hepatica: experimental long-term follow-up of biochemical markers

Abstract: The higher F. gigantica pathogenicity contrasts with previous studies which only reflected the faster development of F. hepatica observed in short-term experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 38 publications
0
53
0
Order By: Relevance
“…According to Pavlović et al [27], high ALP levels, as well as significantly elevated eosinophilia and low hemoglobin, are the most significant laboratory features of human fascioliasis, as was in the main case presented here. However, Valero et al [8] found that γ-glutamyl transferase (GGT) provides information on penetration of young flukes into the bile ducts of sheep. GGT is the best marker, while AST is less sensitive [28].…”
Section: Discussionmentioning
confidence: 99%
“…According to Pavlović et al [27], high ALP levels, as well as significantly elevated eosinophilia and low hemoglobin, are the most significant laboratory features of human fascioliasis, as was in the main case presented here. However, Valero et al [8] found that γ-glutamyl transferase (GGT) provides information on penetration of young flukes into the bile ducts of sheep. GGT is the best marker, while AST is less sensitive [28].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, hybridization may also have serious implications for people living in areas where the two species co‐localize as this could result in the emergence of more pathogenic Fasciola isolates. A recent study by Valero and colleagues showed that when directly compared in infections of Guirra sheep, which have similar susceptibilities to both species, F. gigantica was found to be more pathogenic than F. hepatica . Also, a recent analysis of human infections in Vietnam has revealed that hybrids are also able to infect people .…”
Section: Hybrid And/or Introgressed Populations Of Liver Flukementioning
confidence: 99%
“…Additionally, reinfection has also been related to high pathogenicity and impressive manifestations in patients whether directly by immunologically stimulating the ectopic migration of invasive juvenile flukes or indirectly by increasing complex mechanisms involved in immuno-allergic and toxic processes caused by flukes in the liver but acting systemically at distance [4]. Clinical studies have shown this disease to be pronouncedly complex, giving rise to progressive general deterioration of the patients, with sequelae sometimes leaving subjects handicapped and frail, even leading to fatal cases [2,4,7]. …”
Section: Introductionmentioning
confidence: 99%